Keselarasan Kearifan Lokal Dengan Nilai Keislaman Pada Tradisi Labuhan Gunung Kombang di Kabupaten Malang - Fitria Shalza Rahmaniar; Suyitno Suyitno; Supana Supana; Kundharu Saddhono (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Local wisdom has values that often become the source of norms formation for people's life. Among them is the tradition of Labuhan Gunung Kombang in Malang. This study intended to reveal the Labuhan Gunung Kombang's local wisdom that grows and develops in harmony with Islamic values in Kedungsalam Village, Donomulyo, Malang. This is a descriptive qualitative research by employing ethnographic methods. Data were collected through observations, interviews and documentations to produce detailed and comprehensive accounts of different cultural and social phenomena. The result of study showed that local wisdom of Labuhan Gunung Kombang tradition has values of religion, togetherness, deliberation and mutual cooperation that are in line with Islamic teachings. Islam as a religion with a set of values and norms has influenced the patterns of culture and traditions for Kedungsalam people. However, the encounter of Islamic values and local wisdom in Labuhan Gunung Kombang ceremony is usually perceived as the process of cultural acculturation. It makes socio-cultural aspects of the local people not necessarily eroded by Islam.